Pengelolaan Pembelajaran Tematik di SD Kemasan I No. 64 Surakarta - Budi Utomo; Eko Supriyanto; Wafrotur Rohmah (Universitas Muhammadiyah Surakarta, 2017)
This study describes how teachers grade I, II, and III SDN Kemasan I Surakartamanage thematic learning from planning, implementation, assessment and anyobstacles encountered. This research used qualitative research with researchsubjects principals, teachers of class I, II, and III. The data collection techniqueare by interview, documentation, observation, and questionnaires. Data analysistechnique used is interactive analysis model, namely through data collection, datareduction, data presentation and the conclusion. To obtain such data validity, thenused triangulation. The results showed that in planning the teacher has not madea competency mapping as it should. On implementation, the learning is dominatedby teachers and materials are still fragmentary. Learning has not centered on thetheme and learners. The types of assessment used by teachers are a field test, multiple choice and description. Teachers assessed only on the cognitive domain alone while on the affective and psychomotor yet done. Teachers are still obstacles to the plan that is preparing a syllabus of thematic learning. Another obstacle encountered in the implementation of the teacher is still difficulty in creating a student-centered learning and the lack of teaching aids also be a limiting factor in the implementation of thematic learning in SDN Kemasan I Surakarta.